Effect of Cryoprotectants on Vitrification of Meloidogyne incognita and Heterorhabditis indica on Survival and Infectivity (Indian Journal of Nematology, 2024)
Out of eight cryoprotectants viz. ethylene glycol (10 and 20%), glycerol (15 and 20%), dimethyl sulfoxide (10 and 20%), glycerol (15%) + methanol (70%) and glycerol (20%) + methanol (70%) tested for cryopreservation, for a period of one week, 10% ethylene glycol for Meloidogyne incognita and 20% ethylene glycol for Heterorhabditis indica were found to be the most efficient in providing 14.43 and 11.25% survival, respectively. It was followed by 20% DMSO in providing 11.15% survival of H. indica and 14.13% survival of M. incognita. The cryo infective juveniles of M. incognita and H. indica recovered after 14, 28 and 56 days of preservation in liquid nitrogen did not lose their infectivity and were able to penetrate and reproduce on tomato seedlings and Galleria larvae, respectively. Effect of vitrification of M. incognita eggs did not provide any encouraging results. After thawing only 0.43, 0.50 and 0.40 % eggs hatched in 10 % ethylene glycol, 20 % glycerol and 20 % DMSO, respectively, as compared to 51.82% hatching observed in untreated control.